The Alchemy of Happiness in Noordin Hassan's "Tonight, The Turtles Cry": (Alkimia Kebahagiaan dalam "Malam Ini Penyu Menangis" Karya Noordin Hassan) (Malay Literature, 2020)
Current interest in the nature of happiness has made it a new focal point in the study of literature. While in the West it has been analysed in relation to the dramatic form of tragedy, there has been no corresponding research on it within the context of Islamic theatre. As the founder of teater fitrah, an Islamic brand of theatre, Noordin Hassan and his plays could prove to be fertile grounds from which the issue of happiness could be explored. Hence, this paper aims to discuss Noordin's play, "Tonight, the Turtles Cry" (1994), from an Islamic conceptual framework for happiness as derived from two philosophers, al-Ghazali and al-Attas. Al-Ghazali's The Alchemy of Happiness (1910) and Ihya' 'Ulum-id-Din (1982) as well as al-Attas' "The Meaning and Experience of Happiness" (2014) provide the main theoretical texts from which this framework is taken. Elements of this framework consists of the following: knowing oneself, knowing Allah SWT, knowing this world, which includes ways on building and developing one's relationship with one's family and community, having an appreciation for nature and, finally, having a strong conviction in the hereafter. The analysis used is through close reading of the text. The findings of this paper show significant aspects of Noordin's play as reflecting these components of happiness and showcasing values that are needed to sustain the wellbeing of a person.Keywords: Happiness, Noordin Hassan, al-Ghazali, al-Attas, Islamic theatre